2020
DOI: 10.1108/et-12-2019-0273
|View full text |Cite
|
Sign up to set email alerts
|

Extending the debate over entrepreneurial education effectiveness: the case of a Saudi university

Abstract: PurposeThis study aims to assess the effectiveness of entrepreneurial education (EE) through its impact on the predictor of behavior, which is entrepreneurial intention (EI), by studying the context of a Saudi university, in this case, Umm Al Qura University (UQU). The research theorizes a relationship between EE, innovativeness (INN) as a dimension of personality traits (PTs), and EI, mediated by entrepreneurial motivation (EM). Additionally, in this study, INN played a mediator role between EE and EI.Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 94 publications
(97 reference statements)
3
8
0
Order By: Relevance
“…Similar results have also been obtained previously, which states that good entrepreneurship education can encourage students to take higher entrepreneurial behavior (Ho et al, 2014). The results of this study are also strengthened by the results of research finding that the variable of entrepreneurship education has a positive and significant influence on the variable of entrepreneurial behavior (Ayed, 2020;Howorth et al, 2012).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Similar results have also been obtained previously, which states that good entrepreneurship education can encourage students to take higher entrepreneurial behavior (Ho et al, 2014). The results of this study are also strengthened by the results of research finding that the variable of entrepreneurship education has a positive and significant influence on the variable of entrepreneurial behavior (Ayed, 2020;Howorth et al, 2012).…”
Section: Discussionsupporting
confidence: 56%
“…Research on the effect of entrepreneurship education on entrepreneurial behavior has been previously investigated by several researchers (Ahmed et al, 2019;Alkhalaf et al, 2022;Anosike, 2018;Ho et al, 2014;Moraes et al, 2022;White et al, 2022). The results that entrepreneurship education is indeed able to create entrepreneurial behavior on students (Ayed, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research attempted to investigate the effectiveness of entrepreneurial education in the context of Saudi universities, and results were found to be satisfactory, including student satisfaction and success in the entrepreneurship course, which may be inadequate constructs of entrepreneurial educational effectiveness (Ge et al, 2017;Ayed, 2020). Moreover, Fellnhofer and Puumalainen (2017) showed that involvement in an entrepreneurship program substantially increased the perceived viability of starting up a company.…”
Section: Introductionmentioning
confidence: 99%
“…Questions were based on theoretical analysis and the aim of the research. The questions sought to distinguish how respondents can define entrepreneurship (entrepreneurship definition is analysed in the studies of Turner (2004); Wicham (2006); Skulskis (2012); Stripeikis (2008); Čiburienė, Guščinskienė (2009); Žibėnienė ( 2014 2020)), which are the worrying factors of building a business during a pandemic (Kuckertz et al, 2020;Al Issa (2020)), which teaching methods promote entrepreneurship in higher education (Johann et al (2020); Kim et al (2020); Bacq et al (2020); Yu, 2020), which measures can help develop entrepreneurship in higher education (Muñoz-Castro (2019); Gautam, Singh (2015); Ayed (2020)). The binary scales method consisting of binary items that assume one of the two possible values was used.…”
Section: Online Entrepreneurship Education During a Pandemic Research Objective And Methodologymentioning
confidence: 99%
“…Gautam, Singh (2015) claim that the entrepreneurship education is the exploration of the source of opportunities and the process of discovery in which a person strives for creativity, takes risks, and turns ideas into action. According to Ayed (2020), entrepreneurial education and innovativeness can evoke entrepreneurial intention. Miranda et al (2020) analyze the entrepreneurship education in the context of multidisciplinary collaboration: sociology, psychology, philosophy, business, and engineering education.…”
Section: Theoretical Background Of the Entrepreneurship Educationmentioning
confidence: 99%